EFFECTS OF STARVATION ON THE PROXIMATE CHEMICAL COMPOSITION OF THE JUVENILES BUNNYI BARBUS SHARPEYI - MAHDI, A.A. (Iraqi Journal of Aquaculture, 2022)
Juveniles bunnyi Barbus sharpeyi were subjected to starvation for a period of 11weeks, the proximate chemical analysis of body composition showed that the main effect of starvation was found on the depletion in lipid content, followed by gradual protein decreasing, coincided with an increase in both moisture and ash content. Muscle lipid was the more storage of reserve than that of viscera, that’s why the lost weight from muscles was more. This shows that energy utilized was derived from lipid catabolism in muscle more than viscera. Both condition factor (K) and viscera somatic index (VSI) tend to progressive decrease as starvation period proceded, and there was an inverse relationship between moisture and lipid content in whole specimen.